Electronic Information and Transaction Law, a means of information control in libraries - Nafisah, Syifaun (Universitas Padjadjaran, 2023)
The Ministry of Communication and Information of the Republic of Indonesia reported increased hoax news in society. Libraries as information management institutions require information control tools so that the information served complies with legal and ethical principles. Various problems often occur in libraries, such as copyright infringement and the discovery of adult content in children’s collections. The Law on libraries regulates collection management but does not explicitly stipulate what collections are permitted and prohibited. This study aims to find out Electronic Information and Transaction Law, a means of information control in libraries. This research used the content analysis method. It used quick note techniques and member checks to obtain data. Data analysis used the Miles and Huberman model. Data validation was performed through credibility testing using triangulation, transferability, dependability, and confirmability. According to the Law, legal and ethical information do not violate Intellectual Property Rights and moral norms and protect personal rights. Information also does not contain gambling, insults, defamation, extortion, violence, or threats. Information was also not fake, misleading, or hateful news. The information must be relevant, not derived from wiretapping, and free from content prohibited by the State. Based on these findings, libraries can adopt Law Number 19 of 2016 concerning Electronic Information and Transactions as a tool for information constraints because it follows the goals of libraries to provide legal and ethical information services.